2021
DOI: 10.1088/1748-605x/abe5fa
|View full text |Cite
|
Sign up to set email alerts
|

Biocompatibility of nanomaterials and their immunological properties

Abstract: Nanomaterials (NMs) have revolutionized multiple aspects of medicine by enabling novel sensing, diagnostic, and therapeutic approaches. Advancements in processing and fabrication have also allowed significant expansion in the applications of the major classes of NMs based on polymer, metal/metal oxide, carbon, liposome, or multi-scale macro-nano bulk materials. Concomitantly, concerns regarding the nanotoxicity and overall biocompatibility of NMs have been raised. These involve putative negative effects on bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
46
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(46 citation statements)
references
References 276 publications
0
46
0
Order By: Relevance
“…After injection of TiO 2 NPs, endothelial cells can be disrupted, and they can proliferate and migrate despite the induction of toxicity and immunogenicity. It has been shown that TiO 2 NPs injected into the blood during photothermal cancer therapy enrich the cancer tissue by diffusing, engulfing the cancer cells, and eventually killing them completely [ 47 , 48 , 49 ].…”
Section: Modes Of Exposurementioning
confidence: 99%
See 1 more Smart Citation
“…After injection of TiO 2 NPs, endothelial cells can be disrupted, and they can proliferate and migrate despite the induction of toxicity and immunogenicity. It has been shown that TiO 2 NPs injected into the blood during photothermal cancer therapy enrich the cancer tissue by diffusing, engulfing the cancer cells, and eventually killing them completely [ 47 , 48 , 49 ].…”
Section: Modes Of Exposurementioning
confidence: 99%
“…When it comes to the issue of skin permeation, long-term skin exposure to TiO 2 NPs can be harmful to humans if they overdose, which is almost impossible in everyday life [ 146 ]. Biocompatibility refers to the testing of TiO 2 NPs for cytotoxicity, genotoxicity, immunotoxicity, systemic toxicity, hemocompatibility, pyrogenicity, and implantation, evaluated by ISO, ISO/TR 10993-22:2017 via in vitro and in vivo studies [ 47 ]. The evaluation of the toxicity and biocompatibility of TiO 2 NPs is crucial to understanding the deleterious biological responses of the properties of TiO 2 NPs, their functionalities, and their contact surfaces ( Figure 10 a).…”
Section: Biocompatibility Of Tio 2 Npsmentioning
confidence: 99%
“…When nanoparticles are designed for biomedical applications, the toxicity and biocompatibility of the nanomaterials should be considered carefully. , This consideration is especially important because a smaller size can offer an easier option to interact with biological interfaces via an easier migration, mild toxicity issues can lead to adverse biological effects due to excessive exposure, large-scale use of materials could invite environmental pollution, and any human application requires insignificant toxicity. The toxicity of nanoparticles arises primarily for four specific reasons.…”
Section: Preparation Of Nanoscale Architectures For Biomedical Applic...mentioning
confidence: 99%
“…As mentioned earlier, the inflammatory response, driven by the innate immune system, plays a major role in nanomaterial-induced toxicity. During the last couple of decades, a wealth of compelling evidence has been gathered to support the idea that immune responses to biomaterials have a great impact on their biological activity and toxicological effects [ 60 , 61 , 62 , 63 ]. Industries are designing more advanced materials, which means that more workers and consumers will be exposed to nanoscale particles, posing a risk of detrimental effects on natural systems and ultimately on humans.…”
Section: Immunotoxicitymentioning
confidence: 99%